The Sourcing Process in Casino Gambling’s Player of Thai-Cambodian Borders - KAENMANEE, Sumeth; KHERMKHAN, Jeeranun (Journal of Environmental Management and Tourism; Vol 7 No 1 (2016): JEMT Volume VII, Issue 1(13) Spring 2016, 2016)
The purpose of this paper explore souring process of persuade and attract tourism and gambling in Cambodia’s casino of border Thailand. Moreover, it can show factor succeed in persuading and allow know the behavior of tourists and gamblers. The finding show that gambling across the border in Thailand - Cambodia has a clear system on providers within the cross-border gambling network such as capitalists who are investing as a broker to buy promotion chip, retail travel agents who create networks for exchanging tourists between the company, travel agency's owner and tourists, van drivers, gambling players, travel planner, and owner of the casino. This is the creation of vertical relationship which implies the use of power and patronage system, and there is no trustworthy as it is living with the reciprocal benefits or it can be called that one party patronages another party.
Keywords: casino, sourcing process, Thai-Cambodian borders, gambling